2020
DOI: 10.1080/10428194.2020.1719091
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life results from the IFM 2009 trial: treatment with lenalidomide, bortezomib, and dexamethasone in transplant-eligible patients with newly diagnosed multiple myeloma

Abstract: The Intergroupe Francophone du Myelome 2009 trial (NCT01191060) assessed health-related quality of life (HRQoL) in patients with newly diagnosed multiple myeloma (NDMM) receiving lenalidomide/bortezomib/dexamethasone (RVd) induction therapy followed by consolidation therapy with either autologous stem cell transplantation (ASCT) plus RVd (RVd-ASCT) or RVdalone; both groups then received lenalidomide maintenance therapy for 1 year. Global HRQoL, physical functioning, and role functioning scores significantly im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…14,15 Roussel, et al studied QOL recovery in patients with newly diagnosed MM treated with induction chemotherapy with lenalidomide/ bortezomib/dexamethasone followed by AHCT or induction alone, with both groups receiving lenalidomide maintenance for 1 year. 16 This study had a similar mean age at baseline (56. the shorter time of maintenance lenalidomide. Our analysis showed that overall QOL trajectories are similar to those described by Roussel, et al and remain stable with longer time on maintenance.…”
Section: Discussionmentioning
confidence: 93%
“…14,15 Roussel, et al studied QOL recovery in patients with newly diagnosed MM treated with induction chemotherapy with lenalidomide/ bortezomib/dexamethasone followed by AHCT or induction alone, with both groups receiving lenalidomide maintenance for 1 year. 16 This study had a similar mean age at baseline (56. the shorter time of maintenance lenalidomide. Our analysis showed that overall QOL trajectories are similar to those described by Roussel, et al and remain stable with longer time on maintenance.…”
Section: Discussionmentioning
confidence: 93%
“…The results of the IFM 2009 clinical trial suggest that induction and ASCT followed by maintenance provide improvement in quality of life for NDMM patients. (32) Therefore, it is important to weigh the benefit of prolonged maintenance therapy against the cost of therapy, risk of toxicity and adverse effects. Disease heterogeneity may be an additional consideration in treatment decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients who experienced fewer adverse effects had a longer PFS and OS [58]. As regards the effect of timing of transplant on QoL, similar outcomes were observed in upfront and delayed ASCT groups following VRd induction [59].…”
Section: Other Considerations With Asctmentioning
confidence: 63%